2022
DOI: 10.3233/jad-215467
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State Electroencephalography and P300 Evidence: Age-Related Vestibular Loss as a Risk Factor Contributes to Cognitive Decline

Abstract: Background: In recent years, there have been several meaningful advances in the understanding of the cognitive effects of vestibular loss. However, there has not yet been an investigation exploring the early biomarkers of preclinical cognitive decline in individuals with age-related vestibular loss. Objective: We aim to explore the “early biomarkers” of preclinical cognitive decline based on altered cortical activity (resting-state electroencephalography (EEG) and P300) with a multichannel EEG system in indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
0
8
2
Order By: Relevance
“…There is a decrease in functional connectivity between the cortical Brodmann fields (right wedge-shaped area and left parietal gyrus), which may be 'early biomarkers' of visuospatial, executive functions and attention hypofunction. These features have been associated with decreased P300 amplitude in these areas [23], but this pattern was not present in our study due to the various CVEs in the groups.…”
Section: Discussioncontrasting
confidence: 72%
“…There is a decrease in functional connectivity between the cortical Brodmann fields (right wedge-shaped area and left parietal gyrus), which may be 'early biomarkers' of visuospatial, executive functions and attention hypofunction. These features have been associated with decreased P300 amplitude in these areas [23], but this pattern was not present in our study due to the various CVEs in the groups.…”
Section: Discussioncontrasting
confidence: 72%
“…Moreover, we hypothesized that (2) specific neurometabolic markers of neurodegeneration (tNAA/tCr) and neuroinflammation (mIns/tCr and tCho/tCr) in the hippocampus would predict worse balance performance of older individuals with MCI more than normative older adults. The latter hypothesis is supported by a number of observations indicating that accelerated neurodegenerative processes in the hippocampus interrupt vestibular functioning, specifically in individuals with MCI ( Jacob et al, 2020 , Micarelli et al, 2017 , Micarelli et al, 2018 , Semenov et al, 2016 , Wang et al, 2022 , Wei et al, 2018 , Wei et al, 2019 ). We further examined the neurometabolic correlates of balance control in relation to measures of tNAA/tCr, tCho/tCr, mIns/tCr, and Glx/tCr in prefrontal, posterior cingulate, and sensorimotor regions due to their expected involvement in attentional control of balance ( Petrigna et al, 2021 , Sugihara et al, 2021 ).…”
Section: Introductionmentioning
confidence: 84%
“…A number of these studies have reinforced and extended our understanding of the cognitive effects of vestibular dysfunction (4-8, 10). New evidence has been reported on the possible association between vestibular dysfunction and AD (16), as well as vestibular deficits as possible biomarkers for the disease (18)(19)(20). Although Dordevic et al (15) reported no significant change in hippocampal volume associated with vestibular loss, Cohen et al (16) found that in AD patients, cervicalevoked myogenic potential deficits were associated with a reduction in the volume of the left hippocampus.…”
Section: Discussionmentioning
confidence: 99%